Contribution of Arnett's inventory of sensation seeking and Zuckerman's sensation seeking scale to the differentiation of athletes engaged in high and low risk sports - Zarevski, Predrag; Marušić, Iris; Zolotić, Sanja Bunjevac, Tomislav; Vukosav, Željko (1998)
AISS (Arnett, 1994) and Zuckermans SSS scales were administered on 94 pairs of males between 17 and 47 years of age (M = 29.6 years) from Zagreb, capital of Croatia. Pairs were equivalent in age and education. The independent variable is the risk level of the sports they are engaged in (high risk sports were parachuting, diving, gliding, speleology and alpinism, while low risk sports were athletics, rowing, bowling and table tennis). The aim was to find out which of these two scales is better at discriminating the two groups of athletes, since this is an important test of criterion validity for these two operationalizations of sensation seeking construct. Univariate F ratios show that all six predictors significantly differentiate the criterion groups on p < 0.05 level. In the discriminant analysis almost all of the valid discriminant variance is accounted for by three Zuckerman's subscales - ES, TAS and BS. This finding is even clearer in stepwise regression analysis, where only ES and TAS remain as significant predictors.
Projekt MZOS
ENG